The Cold War Era: The Race for Medical Devices and Health Technologies and Its Global Impact - Tengku Syifa Maulana; Maulia (Journal of Health and Multidisciplinary Health Studies, 2026)
The Cold War was a global conflict that emerged after World War II and involved two major powers, the United States and the Soviet Union. This conflict did not escalate into a large-scale open war but was manifested through ideological, political, economic, and military rivalry, as well as competition for influence in various regions of the world. This article aims to analyze the background of the Cold War, the forms of conflict that arose, and its impacts on the international political order and developing countries. The study employs the historical method with a descriptive-analytical approach through a literature review of relevant academic sources. The findings indicate that the Cold War not only shaped a bipolar pattern of international relations but also influenced regional political dynamics through the emergence of proxy conflicts and the formation of various military alliances. The end of the Cold War in the early 1990s marked the beginning of a new phase in international relations, characterized by shifts in the global power configuration and transformations in patterns of interstate interaction.